Food and feeding habits of Glossogobius giuris from Gosthani estuary - Rao, L M; Rao, P Sankara (Indian Journal of Fisheries, 2011)
Glossogobius giuris - a gobiid, supports an important fishery in the Gosthaniestuary adjacent to Bhimili in the east coast of India and contributes considerablyto the fish-catch throughout the year. Even though it is basically an estuarinefish, occurs quite frequently in fresh waters too. The food and feeding habitsof this fish have been closely followed for about one year. It was observed tofeed on copepods, cladocerans, post larvae and juveniles of shrimp, insect larvae,polycheates, fish-fry etc. This fish occurs in the shrimp and fish cultureponds in considerable numbers, where it not only competes for food and spacebut also preys upon them, thereby causing severe losses to the culturists. Thefood preference of this fish showed some variations and most often it was foundto be cannibalistic.